V. I. Dahl and A. F. Pogosskiy: convergence points in creativity (“A skilled craftsman will not get lost anywhere” and “Daughter of the major”) - Oleg Rostov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2021)
In texts of “great” literature and fi ction of the post-reform period, the commoner — peasant, workman, soldier — became the main character. Accordingly, critics raised a question about suffi ciency of their literary refl ection, about the educational role and addressee of these texts. In this regard, there arose new problems associated with the notions of “folk literature”, “literature about the people and for the people”, as well as the notions of “soldier’s writers”, “soldier’s literature”, and “war book”. V. I. Dal and A. F. Pogossky also looked for techniques and methods of the reasonable portrayal of a commoner, tried to fi nd “approaches” to his soul, heart, and mind. Both of them, in one way or another, identifi ed themselves and their work with those people, including the military, who they described and for whom they designed their books. They claimed that they were able to see the world through the eyes of a commoner, to speak in his language, to “feel at home” in soldiers’ environment. Besides, contemporaries saw an almost direct link between Dahl and Pogossky, the latter being called the “military Dahl”. The article reveals the elements of similarity and diff erence in the stories of the “two Dahls” about soldiers who obtained the skill of reading and writing. It is shown that the diff erence in the fates of these characters is determined not only by “pure accident”, but also by the context of “before and now”, as well as the dissimilarity of the educational priorities of Dahl and Pogossky in terms of advantages and disadvantages of literacy for the commoner.